Investigating the Role of Fish and Fishing in Sharing Networks to Build Resilience in Coral Reef Social-Ecological Systems. Issue 3 (3rd May 2020) - Dacks, Rachel; Ticktin, Tamara; Jupiter, Stacy D.; Friedlander, Alan M.
Abstract: Social networks have been and remain important in Oceania for building and maintaining social-ecological resilience. However, there is little quantitative information on the role of fish and fishing in resource sharing networks and how networks may be impacted by socioeconomic and environmental changes, which is critical information for developing culturally appropriate fisheries management strategies. To better understand this gap, we conducted social network analysis of sharing networks in 18 villages in Fiji across a socioeconomic gradient. Villages formed two clusters based on network characteristics: villages on the main island had less cohesive networks with more cash and purchased good sharing, while villages located on other islands had more cohesive networks with a greater proportion of natural resource sharing. Metrics of network cohesion were positively correlated with mean household fishing frequency and negatively correlated with measures of material wealth. Fishers reported sharing the largest estimated catch from gillnets and night spearfishing. Given concerns about the sustainability of these fishing practices, we suggest methods for regulating these gears while maintaining fish sharing customs. This study shows how social network analysis can be conducted to better understand sharing networks to support natural resource management.